Liver chemistries in glycogenic hepatopathy associated with type 1 diabetes mellitus: A systematic review and pooled analysis. (28th February 2021) - Haffar, Samir; Izzy, Manhal; Habib, Hany; Sugihara, Takaaki; Li, Darrick K.; Sharma, Ayush; Wang, Zhen; Murad, M. Hassan; Watt, Kymberly D.; Bazerbachi, Fateh
Abstract: Background & Aims: Glycogenic hepatopathy (GH) in type 1 diabetes‐mellitus (T1DM) is characterized by hepatomegaly and perturbations of liver chemistries (LC) that have not been well studied. Furthermore, misdiagnosis with other hepatic complications of T1DM, such as nonalcoholic fatty liver disease, has been described. We perform a systematic review of biopsy‐proven GH reports in T1DM patients to identify LC patterns. Methods: A systematic review identified reports of biopsy‐proven GH in patients with T1DM. We excluded GH with other liver diseases, Mauriac syndrome, or GH without T1DM. Two reviewers screened and extracted studies and assessed their methodological quality. LC elevation magnitude, AST‐to‐ALT ratio, R‐ratio to designate hepatocellular, cholestatic or mixed pattern of hepatic injury, and evolution of transaminases after glycemic control were analyzed. Results: A total of 192 patients were included, with median age of 20 years, 73% adults, 66% females, median duration of T1DM before diagnosis 10 years, median adult body mass index 21 kg/m 2, median HbA1c 12%, at least one episode of diabetic ketoacidosis 70%, and hepatomegaly 92%. ALT and AST showed moderate‐to‐severe elevation in 78% and 76%, respectively, AST/ALT >1 in 71% and hepatocellular to mixed pattern of hepatic injury in 81%. Transaminase improvement with glycemic control was the rule, regardless of other factors in multilinear regression analysis. Conclusion: GH tends to have AST‐predominant elevation with a median of 13 times the upper normal limit and R‐ratio >2, which may distinguish it from other etiologies of AST‐predominant LC elevation, and in the appropriate clinical context, may obviate invasive tests.